Humanization of nursing care for the elderly in Primary Care: an integrative review - Torres, Jeruzia Pinheiro (2021)
Currently, the aging process is understood as a challenge for public health worldwide, given the sharp increase in the elderly population. The objective was to analyze the scientific production about the humanization of nursing care for the elderly in the context of Primary Care. This is an integrative review, comprising national studies published between 2011 and 2020, on the Virtual Health Library portal. The search and selection of articles took place from May to June 2021, by crossing descriptors and using the operator Boolean: “Assistência de Enfermagem” and “idoso” and “humanização”. In the search, a total of 160 articles can be obtained, after applying the filters, 68 remained for analysis. After reading, analyzing and applying the inclusion and exclusion criteria under the 68 studies, 18 articles remained to compose the sample. After analyzing the studies, two categories emerged: 1 - Humanized nursing care for the elderly in the context of Primary Care and; 2 - Main obstacles faced by nurses to provide care for the elderly in a humane way in Primary Care. Based on the results obtained, the importance of care can be seen to humanize the elderly, as well as the existence of difficulties that still prevent nursing professionals from offering this assistance. Therefore, it is necessary to implement public policies for this population, in order to ensure humanized care, envisioning healthy and quality aging, in addition to training professionals in the area of ​​geriatrics and gerontology.